2013
DOI: 10.1111/echo.12468
|View full text |Cite
|
Sign up to set email alerts
|

Septal Curvature Is Marker of Hemodynamic, Anatomical, and Electromechanical Ventricular Interdependence in Patients with Pulmonary Arterial Hypertension

Abstract: Septal curvature is a useful marker of structural, hemodynamic, and electromechanical ventricular interdependence in PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 28 publications
2
42
0
2
Order By: Relevance
“…27 In addition, an assessment of septal curvature by using a systolic eccentricity index enabled the differentiation of patients with pulmonary arterial hypertension from healthy subjects. 28 This study also demonstrated that patients with pulmonary arterial hypertension with higher eccentricity index values had worse ventricular function and lower exercise capacity.…”
Section: Discussionsupporting
confidence: 51%
“…27 In addition, an assessment of septal curvature by using a systolic eccentricity index enabled the differentiation of patients with pulmonary arterial hypertension from healthy subjects. 28 This study also demonstrated that patients with pulmonary arterial hypertension with higher eccentricity index values had worse ventricular function and lower exercise capacity.…”
Section: Discussionsupporting
confidence: 51%
“…29,30 Hemodynamic parameters (MAP and MPAP) were recorded at times corresponding to blood collection, and the MAP/MPAP ratio was calculated as a pharmacodynamic marker. 37,38 Noncompartmental analysis was subsequently performed on PK and PD data using Phoenix TM software (Certara, St. Louis, MO, USA). The non-compartmental analysis was performed using plasma and drug effect models with uniform weighting and intravenous infusion dosing.…”
Section: Pharmacokinetic and Pharmacodynamic (Pd) Substudymentioning
confidence: 99%
“…18,19 Basic assessment of the cardiopulmonary unit by echocardiography involves assessment of cardiac chamber size; metrics of RV function such as tricuspid annular plane systolic excursion, fractional area change, and myocardial performance indexes; valvular regurgitation or function; pulmonary hemodynamics; and septal curvature, which can integrate metrics on ventricular interdependence. 16,20,21 Table 2 summarizes normative values for the measures of function of the right side of the heart, and Figure 2 illustrates some of these measures. 16,[22][23][24][25][26][27][28][29][30][31] As discussed in the following paragraphs, myocardial deformation imaging is also emerging as a useful modality for imaging the right side of the heart.…”
Section: Overview Of Echocardiographic Evaluationmentioning
confidence: 99%
“…21,[38][39][40][41] Moreover, in future studies, screening algorithms should be tested in patients with very mild pulmonary vascular disease to identify the most reliable early markers of pulmonary vascular disease and dysfunction of the right side of the heart.…”
Section: Circulationmentioning
confidence: 99%